Sensor response to alcohol and chemical mechanism of carbon nanotube gas sensors - Mahdavian L. (2014)
The reaction of ethanol and methanol over carbon nanotubes (CNTs) has been investigated. The main reaction product in all cases is acetaldehyde and formaldehyde, with secondary products such as ethyl acetate and methyl format. CNTs have many distinct properties that may be exploited to develop the next generation of sensors. We study the distinct physical, electronic, and mechanical properties of CNTs. This artivcle aims to act as a reference source for researchers to help them in developing new applications of CNT-based sensors. Interaction between alcohol molecules and CNT is investigated using a semi-empirical MNDO method. We study the total energy, electron, and thermodynamic properties adsorption alcohols on armchair single-walled carbon nanotubes (SWNT (4,4)) obtained at room temperature. In this study presented a comprehensive studying on effects of gases on SWNT that it is on its electronic structure and transfer of charge from the atoms to the SWNT. The ethanol and methanol converted to other oxidation products on SWNT-based sensors.